Answer:
The answer is A. -6x-2y=12.
Explanation:
In order to graph the equation, start by rewriting the equation in slope-intercept form. To rewrite the equation in slope-intercept form, add 6x to both sides of the equation, and then divide each term by -2 and simplify. Now, the equation should look like y= -6-3x.
Using the slope-intercept form, you can find the slope and y-intercept. By using the formula of y= mx+b, m= -3 and b= -6. Thus, the slope is -3 and the y-intercept is (0,-6).
Now, you can create a table of x and y values to graph the equation. After graphing the table of x and y values, the final answer is -6x-2y=12.